Modelling and estimation on vibration and noise level of the dynamic wiper system using input shaping strategy - Salim, Mohd Azli; Md. Saad, Adzni; Akop, Mohd Zaid; Photong, Chonlatee; Md. Zain, Mohd Zarhamdy; Abu Bakar, Abd Rahim; Mohd Yusof, Norbazlan (Penerbit UniMAP, 2021)
During wiping operation to wipe rain and dirt out from the windscreen, the wiper generates unwanted noise and vibration. This may cause dissatisfaction to the automotive vehicles due to annoying sounds and perhaps leads to poor visibility to the driver. Therefore, this paper proposes an approach to reduce and eliminate noise and vibration in a windscreen automotive vehicles wiper system. A two-dimensional mathematical model available in the open literature is adopted and integrated with a proposed control scheme, i.e. input shaping. Firstly, analysis is performed based on an original model, i.e. without input shaping in order to determine the noise (frequency) and vibration (amplitude) levels. Comparison is also made between the prediction results with finite element results. It is found that the correlation is reasonably close. The next stage is to introduce the two-impulse input shaping scheme. It is found that the input shaping could reduce certain amount of vibration level. Finally, parametric studies are also performed to examine the effectiveness of the proposed approach.